Vacuum pump energy-saving rotor machining process

By preparing and using specific coatings in the vacuum pump rotor processing process, combined with hot -melt casting and thermal treatment technology, the vacuum pump rotor mechanical performance and surface defects are difficult to eliminate, and vacuum pump rotors with higher quality and longer life.

CN119328075AActive Publication Date: 2025-01-21SHANDONG ZHONGHAI INTELLIGENT EQUIP CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411482022.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-01-21
Estimated Expiration
2044-10-23

AI Technical Summary

Technical Problem

The mechanical properties of existing vacuum pump rotors are insufficient, and surface defects are difficult to completely eliminate, affecting their quality and service life.

Method used

Adopt a vacuum pump energy saving rotor processing process, including preparing paint and evenly coated on the surface of the cavity. Complete the processing of the rotor.

Benefits of technology

The mechanical properties of the energy-saving rotor of the vacuum pump are significantly improved, surface defects are effectively eliminated, and the quality and quality of the product are improved.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of vacuum pump rotor production, in particular to a vacuum pump energy-saving rotor machining technology. The preparation method comprises the following steps: preparing a coating, uniformly coating the surface of a cavity with the prepared coating, drying, grinding and polishing, melting a rotor raw material in a hot melting form, putting the molten rotor raw material in the cavity, casting and molding, cooling, taking out, grinding and polishing again to obtain a blank, and finally carrying out heat treatment and cooling on the obtained blank to obtain a finished product. The coating is prepared from the raw materials of the composite base material, the aggregate, ethyl cellulose, dodecylphenol polyoxyethylene ether, ethanol and the like. According to the vacuum pump energy-saving rotor machining technology, the mechanical property of a vacuum pump energy-saving rotor can be improved, meanwhile, the excellent surface defect eliminating performance is achieved, and the quality of the vacuum pump energy-saving rotor is effectively guaranteed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of vacuum pump rotor production, and in particular to a vacuum pump energy-saving rotor processing technology. Background Art

[0002] A vacuum pump is a device or equipment that uses mechanical, physical, chemical or physicochemical methods to evacuate the container to obtain a vacuum. In layman's terms, a vacuum pump is a device that uses various methods to improve, generate and maintain a vacuum in a closed space. The screw vacuum pump has a simple structure and is widely used in the fields of chemical industry, pharmaceuticals, petrochemicals, electronics, nuclear power, etc. The vacuum pump rotor is the core component of the pump, and the reliability of the rotor directly affects the service life of the pump.

[0003] In the patent document with application number "CN202211692454.0" and titled "A Casting Process for a Dry Screw Vacuum Pump Rotor", it is recorded that "The present invention uses coating to coat the cavity, including the following steps: 1) the coating is evenly coated on the cavity, dried, and polished with 80-140 mesh coarse sandpaper; 2) the coating in step 1) is added with 1-2 times its volume of volatile solvent, evenly coated on the cavity, dried, and polished with 400-800 mesh sandpaper; 3) the coating in step 1) is added with 2-4 times its volume of volatile solvent, evenly coated on the cavity, dried, and polished with 1000-1200 mesh sandpaper; it can significantly improve the surface quality of the casting."

[0004] Although the casting process of the vacuum pump rotor provided in the above patent document has certain advantages such as improving surface defects, its mechanical properties are relatively insufficient and still need to be further improved. Based on this, the present invention provides a vacuum pump energy-saving rotor processing process to solve the above technical problems. Summary of the invention

[0005] The purpose of the present invention is to provide a vacuum pump energy-saving rotor processing technology. The provided vacuum pump energy-saving rotor processing technology can not only improve the mechanical properties of the vacuum pump energy-saving rotor, but also has excellent surface defect elimination performance, effectively ensuring its quality.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] The present invention provides a vacuum pump energy-saving rotor processing technology, comprising the following steps:

[0008] S1. Prepare a coating, apply the prepared coating evenly on the surface of the cavity, and after drying, polish it with 1000-1200 mesh sandpaper;

[0009] S2, melting the rotor raw material by hot melting, then placing it in the mold cavity for casting, taking it out after cooling, and polishing it again with 1000-1200 mesh sandpaper to obtain a blank;

[0010] S3, after the obtained blank is heat treated and cooled, the processing of the vacuum pump rotor is completed.

[0011] The present invention is further configured as follows: in step S1, the coating is made of the following raw materials in parts by weight: 20 to 30 parts of a composite base material, 8 to 12 parts of aggregate, 4 to 8 parts of ethyl cellulose, 2 to 4 parts of dodecylphenol polyoxyethylene ether and 25 to 35 parts of ethanol;

[0012] The preparation process of the coating is as follows:

[0013] Accurately weigh the composite base material, aggregate, ethyl cellulose, dodecylphenol polyoxyethylene ether and ethanol, place the composite base material, aggregate, ethyl cellulose, dodecylphenol polyoxyethylene ether and ethanol in a mixing device, and mix them at 30-40° C. and 220-320 r / min for 20-30 minutes;

[0014] After the mixing is completed, the obtained material is ball-milled in a ball mill for 1 to 3 hours to obtain a coating.

[0015] The present invention is further configured as follows: the composite base material is formed by mixing polyvinyl butyral and furan resin in a mass ratio of 1:0.08-0.14.

[0016] The present invention is further configured as follows: the aggregate is formed by mixing talcum powder and modified bentonite in a mass ratio of 1:0.22-0.32.

[0017] The present invention is further configured as follows: the preparation process of the modified bentonite is as follows:

[0018] Disperse bentonite in an appropriate amount of deionized water with ultrasonic method at a solid-liquid ratio of 0.12-0.24 g / mL for 20-30 min, add auxiliary materials of 4.8-5.2% of bentonite mass, treat at 340-440 r / min for 30-40 min, and leave to stand for 36-40 h in a sealed container;

[0019] After standing, add 65-75% ethanol of the volume of deionized water, continue to treat at 340-440r / min for 20-30min, filter, dry at 70-80°C for 8-10h to obtain modified bentonite.

[0020] The present invention is further configured as follows: the auxiliary material is selected from any one of lithium carbonate and lithium nitrate.

[0021] The present invention is further configured as follows: the weight ratio of the grinding balls of the ball mill to the material is 8-16:1, and the rotation speed of the ball mill is 50-80 r / min.

[0022] The present invention is further configured as follows: in step S3, the heat treatment process is as follows:

[0023] The first stage: the obtained blank is heated to 550-560°C and kept at this temperature for 240-260 minutes;

[0024] The second stage: cool down to 500-510℃ and keep warm for 100-120min;

[0025] The third stage: Then cool to room temperature to complete the heat treatment of the blank.

[0026] The present invention is further configured as follows: the heating rate in the first stage is 10-14°C / min, the cooling rate in the second stage is 1-3°C / min, and the cooling in the third stage is natural cooling.

[0027] The present invention is further configured as follows: in the step S3, after the obtained blank is heat-treated and cooled, it is also polished with sandpaper of 1000-1200 meshes.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] The present invention prepares a coating, uniformly applies the prepared coating to the surface of the cavity, grinds and polishes it after drying, melts the rotor raw material in the form of hot melt, and then places it in the cavity for casting and molding, takes it out after cooling, grinds and polishes it again to obtain a blank, and finally heat treats the obtained blank and cools it to complete the processing of the vacuum pump rotor, wherein the coating is prepared with composite base material, aggregate, ethyl cellulose, dodecylphenol polyoxyethylene ether and ethanol as raw materials. The vacuum pump energy-saving rotor processing technology provided by the present invention can not only improve the mechanical properties of the vacuum pump energy-saving rotor, but also has excellent surface defect elimination performance, effectively ensuring its quality. The vacuum pump energy-saving rotor processing technology provided by the present invention has a broader market prospect and is more suitable for promotion. DETAILED DESCRIPTION

[0030] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0031] Example 1

[0032] This embodiment provides a vacuum pump energy-saving rotor processing process, comprising the following steps:

[0033] S1. Prepare the coating, apply the prepared coating evenly on the surface of the cavity, and after drying, polish it with 100-mesh sandpaper.

[0034] The coating is made of the following raw materials in parts by weight: 20 parts of composite base material, 8 parts of aggregate, 4 parts of ethyl cellulose, 2 parts of dodecylphenol polyoxyethylene ether and 25 parts of ethanol;

[0035] Furthermore, the coating preparation process is as follows:

[0036] Accurately weigh the composite base material, aggregate, ethyl cellulose, dodecylphenol polyoxyethylene ether and ethanol, place the composite base material, aggregate, ethyl cellulose, dodecylphenol polyoxyethylene ether and ethanol in a mixing device, and mix them at 30°C and 220r / min for 20min;

[0037] After the mixing is completed, the obtained material is ball-milled in a ball mill for 1 hour to obtain a coating.

[0038] Furthermore, the composite base material is mixed with polyvinyl butyral and furan resin in a mass ratio of 1:0.08.

[0039] In this embodiment, it should be noted that polyvinyl butyral was purchased from Jinan Shuangying Chemical Co., Ltd., and furan resin was purchased from Shandong Duoju Chemical Co., Ltd.

[0040] The aggregate is a mixture of talcum powder and modified bentonite in a mass ratio of 1:0.22.

[0041] Furthermore, the preparation process of modified bentonite is as follows:

[0042] Bentonite was ultrasonically dispersed in an appropriate amount of deionized water at a solid-liquid ratio of 0.12 g / mL for 20 minutes, and then 4.8% of the bentonite mass of auxiliary materials were added thereto, and the mixture was treated at 340 r / min for 30 minutes, and then sealed and left to stand for 36 hours;

[0043] After standing, 65% ethanol by volume of deionized water was added thereto, and the mixture was treated at 340 r / min for 20 min. After filtration, the mixture was dried at 70° C. for 8 h to obtain modified bentonite.

[0044] Among them, lithium carbonate is selected as the auxiliary material.

[0045] In this embodiment, it should be noted that talc was purchased from Henan Xinzhiyuan Chemical Products Co., Ltd., and bentonite was purchased from DCH Chemical International Trading (Shanghai) Co., Ltd.

[0046] In addition, the weight ratio of the ball mill to the material is 8:1, and the ball mill speed is 50r / min.

[0047] S2. Melt the rotor raw material by hot melting, then place it in the mold cavity for casting, take it out after cooling, and grind and polish it again with 1000-mesh sandpaper to obtain a blank.

[0048] In this embodiment, the rotor material is iron.

[0049] S3, after the obtained blank is heat treated and cooled, the processing of the vacuum pump rotor is completed.

[0050] The heat treatment process is as follows:

[0051] The first stage: the obtained blank is heated to 550°C and kept at this temperature for 240 minutes;

[0052] The second stage: cool down to 500℃ and keep warm for 100min;

[0053] The third stage: Then cool to room temperature to complete the heat treatment of the blank.

[0054] Furthermore, the heating rate in the first stage is 10°C / min, the cooling rate in the second stage is 1°C / min, and the cooling in the third stage is natural cooling.

[0055] In addition, the method also includes grinding and polishing the obtained blank with sandpaper of 1000 to 1200 mesh after cooling the blank through heat treatment.

[0056] Example 2

[0057] This embodiment provides a vacuum pump energy-saving rotor processing process, comprising the following steps:

[0058] S1. Prepare the coating, apply the prepared coating evenly on the surface of the cavity, and after drying, polish it with 1000-1200 mesh sandpaper.

[0059] The coating is made of the following raw materials in parts by weight: 25 parts of composite base material, 10 parts of aggregate, 6 parts of ethyl cellulose, 3 parts of dodecylphenol polyoxyethylene ether and 30 parts of ethanol;

[0060] Furthermore, the coating preparation process is as follows:

[0061] Accurately weigh the composite base material, aggregate, ethyl cellulose, dodecylphenol polyoxyethylene ether and ethanol, place the composite base material, aggregate, ethyl cellulose, dodecylphenol polyoxyethylene ether and ethanol in a mixing device, and mix them at 35°C and 270r / min for 25min;

[0062] After the mixing is completed, the obtained material is ball-milled in a ball mill for 2 hours to obtain a coating.

[0063] Furthermore, the composite base material is mixed with polyvinyl butyral and furan resin in a mass ratio of 1:0.11.

[0064] In this embodiment, it should be noted that polyvinyl butyral was purchased from Jinan Shuangying Chemical Co., Ltd., and furan resin was purchased from Shandong Duoju Chemical Co., Ltd.

[0065] The aggregate is a mixture of talcum powder and modified bentonite in a mass ratio of 1:0.27.

[0066] Furthermore, the preparation process of modified bentonite is as follows:

[0067] Disperse bentonite in an appropriate amount of deionized water with ultrasonic method at a solid-liquid ratio of 0.18 g / mL for 25 min, add auxiliary materials of 5% by weight of bentonite, treat at 390 r / min for 35 min, and leave it in a sealed container for 38 h;

[0068] After standing, 70% ethanol by volume of deionized water was added thereto, and the mixture was treated at 390 r / min for 25 min. After filtration, the mixture was dried at 75° C. for 9 h to obtain modified bentonite.

[0069] Among them, lithium nitrate is selected as the auxiliary material.

[0070] In this embodiment, it should be noted that talc was purchased from Henan Xinzhiyuan Chemical Products Co., Ltd., and bentonite was purchased from DCH Chemical International Trading (Shanghai) Co., Ltd.

[0071] In addition, the weight ratio of the ball mill to the material is 12:1, and the ball mill speed is 75r / min.

[0072] S2. Melt the rotor raw material by hot melting, then place it in the mold cavity for casting, take it out after cooling, and grind and polish it again with 1100-mesh sandpaper to obtain a blank.

[0073] In this embodiment, the rotor material is iron.

[0074] S3, after the obtained blank is heat treated and cooled, the processing of the vacuum pump rotor is completed.

[0075] The heat treatment process is as follows:

[0076] The first stage: the obtained blank is heated to 555°C and kept at this temperature for 250 minutes;

[0077] The second stage: cool down to 505℃ and keep warm for 110min;

[0078] The third stage: Then cool to room temperature to complete the heat treatment of the blank.

[0079] Furthermore, the heating rate in the first stage is 12° C. / min, the cooling rate in the second stage is 12° C. / min, and the cooling in the third stage is natural cooling.

[0080] In addition, the method further includes grinding and polishing the blank with 1100-grit sandpaper after cooling the blank after heat treatment.

[0081] Example 3

[0082] This embodiment provides a vacuum pump energy-saving rotor processing process, comprising the following steps:

[0083] S1. Prepare the coating, apply the prepared coating evenly on the surface of the cavity, and after drying, polish it with 1200-grit sandpaper.

[0084] The coating is made of the following raw materials in parts by weight: 30 parts of composite base material, 12 parts of aggregate, 8 parts of ethyl cellulose, 4 parts of dodecylphenol polyoxyethylene ether and 35 parts of ethanol;

[0085] Furthermore, the coating preparation process is as follows:

[0086] Accurately weigh the composite base material, aggregate, ethyl cellulose, dodecylphenol polyoxyethylene ether and ethanol, place the composite base material, aggregate, ethyl cellulose, dodecylphenol polyoxyethylene ether and ethanol in a mixing device, and mix them at 40°C and 320r / min for 30min;

[0087] After the mixing is completed, the obtained material is ball-milled in a ball mill for 3 hours to obtain a coating.

[0088] Furthermore, the composite base material is mixed with polyvinyl butyral and furan resin in a mass ratio of 1:0.14.

[0089] In this embodiment, it should be noted that polyvinyl butyral was purchased from Jinan Shuangying Chemical Co., Ltd., and furan resin was purchased from Shandong Duoju Chemical Co., Ltd.

[0090] The aggregate is a mixture of talcum powder and modified bentonite in a mass ratio of 1:0.32.

[0091] Furthermore, the preparation process of modified bentonite is as follows:

[0092] Disperse bentonite in an appropriate amount of deionized water with ultrasonic method at a solid-liquid ratio of 0.24 g / mL for 30 minutes, add auxiliary materials with a mass percentage of 5.2% of bentonite, treat at 440 r / min for 40 minutes, and leave it to stand for 40 hours in a sealed container;

[0093] After standing, 75% ethanol by volume of deionized water was added thereto, and the mixture was treated at 440 r / min for 30 min. After filtration, the mixture was dried at 80° C. for 10 h to obtain modified bentonite.

[0094] Among them, lithium carbonate is selected as the auxiliary material.

[0095] In this embodiment, it should be noted that talc was purchased from Henan Xinzhiyuan Chemical Products Co., Ltd., and bentonite was purchased from DCH Chemical International Trading (Shanghai) Co., Ltd.

[0096] In addition, the weight ratio of the ball mill to the material is 16:1, and the ball mill speed is 80r / min.

[0097] S2. Melt the rotor raw material by hot melting, then place it in the mold cavity for casting, take it out after cooling, and grind and polish it again with 1200-mesh sandpaper to obtain a blank.

[0098] In this embodiment, the rotor material is iron.

[0099] S3, after the obtained blank is heat treated and cooled, the processing of the vacuum pump rotor is completed.

[0100] The heat treatment process is as follows:

[0101] The first stage: the obtained blank is heated to 560°C and kept at this temperature for 260 minutes;

[0102] The second stage: cool down to 510℃ and keep warm for 120min;

[0103] The third stage: Then cool to room temperature to complete the heat treatment of the blank.

[0104] Furthermore, the heating rate in the first stage is 14° C. / min, the cooling rate in the second stage is 3° C. / min, and the cooling in the third stage is natural cooling.

[0105] In addition, the method further includes grinding and polishing the blank with 1200-grit sandpaper after cooling the blank after heat treatment.

[0106] Comparative Example 1: The difference from Example 1 is that no coating is used in this example.

[0107] Comparative Example 2: The difference from Example 1 is that no heat treatment is used in this example.

[0108] Performance test: The energy-saving rotor samples of the vacuum pumps provided in Examples 1 to 3 and Comparative Examples 1 to 2 are marked as Examples 1 to 3 and Comparative Examples 1 to 2, respectively; and the relevant performances of the energy-saving rotors of the vacuum pumps provided in Examples 1 to 3 and Comparative Examples 1 to 2 are tested as follows:

[0109] 1. Surface defect test: The test method is that 10 people use their naked eyes to observe the rotor surface at a 45° angle to the light to evaluate the surface flatness of each rotor. The evaluation results are scored as 3, 2, 1 and 0 to obtain the final total score.

[0110] 2. Compressive strength test: The test method is GB / T13822-1992.

[0111] 3. Elongation test: The samples were tested according to ASTM B577-2019.

[0112] The obtained test data are recorded in Table 1 and Table 2 below:

[0113] Table 1 Surface defect test results of each group of vacuum pump energy-saving rotors

[0114] Group Score Example 1 Group 29 Example 2 Group 27 Example 3 Group 27 Comparison group 1 8 Comparison of 2 groups 16

[0115] Table 2 Mechanical properties test results of each group of vacuum pump energy-saving rotors

[0116] Group Tensile strength(MPa) Elongation(%) Example 1 Group 665 24 Example 2 Group 662 23 Example 3 Group 666 24 Comparison group 1 655 21 Comparison of 2 groups 568 15

[0117] By comparing and analyzing the relevant data in Table 1 and Table 2, it can be seen that the vacuum pump energy-saving rotor processing technology provided by the present invention can not only improve the mechanical properties of the vacuum pump energy-saving rotor, but also has excellent surface defect elimination performance, effectively ensuring its quality. This shows that the vacuum pump energy-saving rotor processing technology provided by the present invention has a broader market prospect and is more suitable for promotion.

[0118] The present invention prepares a coating, uniformly applies the prepared coating to the surface of the cavity, grinds and polishes after drying, melts the rotor raw material in the form of hot melt, then places it in the cavity for casting, takes it out after cooling, grinds and polishes it again to obtain a blank, and finally heat treats the obtained blank and cools it to complete the processing of the vacuum pump rotor, wherein the coating is prepared with composite base material, aggregate, ethyl cellulose, dodecylphenol polyoxyethylene ether and ethanol as raw materials. The provided vacuum pump energy-saving rotor processing technology can not only improve the mechanical properties of the vacuum pump energy-saving rotor, but also has excellent surface defect elimination performance.

[0119] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0120] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A vacuum pump energy-saving rotor processing technology, characterized in that: The following steps are involved: S1. Prepare a coating, apply the prepared coating evenly on the surface of the cavity, and after drying, polish it with 1000-1200 mesh sandpaper; S2, melting the rotor raw material by hot melting, then placing it in the mold cavity for casting, taking it out after cooling, and polishing it again with 1000-1200 mesh sandpaper to obtain a blank; S3, after the obtained blank is heat treated and cooled, the processing of the vacuum pump rotor is completed.

2. A vacuum pump energy-saving rotor processing technology according to claim 1, characterized in that: In the step S1, the coating is made of the following raw materials in parts by weight: 20 to 30 parts of composite base material, 8 to 12 parts of aggregate, 4 to 8 parts of ethyl cellulose, 2 to 4 parts of dodecylphenol polyoxyethylene ether and 25 to 35 parts of ethanol; The preparation process of the coating is as follows: Accurately weigh the composite base material, aggregate, ethyl cellulose, dodecylphenol polyoxyethylene ether and ethanol, place the composite base material, aggregate, ethyl cellulose, dodecylphenol polyoxyethylene ether and ethanol in a mixing device, and mix them at 30-40° C. and 220-320 r / min for 20-30 minutes; After the mixing is completed, the obtained material is ball-milled in a ball mill for 1 to 3 hours to obtain a coating.

3. A vacuum pump energy-saving rotor processing technology according to claim 2, characterized in that: The composite base material is prepared by mixing polyvinyl butyral and furan resin in a mass ratio of 1:0.08-0.

14.

4. A vacuum pump energy-saving rotor processing technology according to claim 2, characterized in that: The aggregate is prepared by mixing talcum powder and modified bentonite in a mass ratio of 1:0.22-0.

32.

5. A vacuum pump energy-saving rotor processing technology according to claim 3, characterized in that: The preparation process of the modified bentonite is as follows: Disperse bentonite in an appropriate amount of deionized water by ultrasonic at a solid-liquid ratio of 0.12-0.24 g / mL for 20-30 min, add auxiliary materials of 4.8-5.2% of bentonite mass, treat at 340-440 r / min for 30-40 min, and leave to stand in a sealed container for 36-40 h; After standing, add 65-75% ethanol of the volume of deionized water, continue to treat at 340-440r / min for 20-30min, filter, dry at 70-80℃ for 8-10h to obtain modified bentonite.

6. A vacuum pump energy-saving rotor processing technology according to claim 5, characterized in that: The auxiliary material is selected from any one of lithium carbonate and lithium nitrate.

7. A vacuum pump energy-saving rotor processing technology according to claim 2, characterized in that: The weight ratio of the grinding balls of the ball mill to the material is 8-16:1, and the rotation speed of the ball mill is 50-80 r / min.

8. A vacuum pump energy-saving rotor processing technology according to claim 1, characterized in that: In step S3, the heat treatment process is as follows: The first stage: the obtained blank is heated to 550-560°C and kept at this temperature for 240-260 minutes; The second stage: cool down to 500-510℃ and keep warm for 100-120min; The third stage: Then cool to room temperature to complete the heat treatment of the blank.

9. A vacuum pump energy-saving rotor processing technology according to claim 8, characterized in that: In the first stage, the heating rate is 10-14°C / min, in the second stage, the cooling rate is 1-3°C / min, and the cooling in the third stage is natural cooling.

10. A vacuum pump energy-saving rotor processing technology according to claim 1, characterized in that: In the step S3, the method further comprises grinding and polishing the blank with sandpaper of 1000-1200 mesh after the blank is heat treated and cooled.

Citation Information

Patent Citations

  • Casting process of dry type screw vacuum pump rotor

    CN115770860A

  • Heat-insulating, heat-preserving and sound-insulating coating and preparation method thereof

    CN116535910A